2012
DOI: 10.1016/j.bpj.2012.08.039
|View full text |Cite
|
Sign up to set email alerts
|

A Deconvolution-Based Method with High Sensitivity and Temporal Resolution for Detection of Spontaneous Synaptic Currents In Vitro and In Vivo

Abstract: Spontaneous postsynaptic currents (PSCs) provide key information about the mechanisms of synaptic transmission and the activity modes of neuronal networks. However, detecting spontaneous PSCs in vitro and in vivo has been challenging, because of the small amplitude, the variable kinetics, and the undefined time of generation of these events. Here, we describe a, to our knowledge, new method for detecting spontaneous synaptic events by deconvolution, using a template that approximates the average time course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 38 publications
(66 reference statements)
3
77
0
Order By: Relevance
“…Briefly, events were detected using a template-based search (Pernía-Andrade et al, 2012), aligned by their point of steepest rise and peak scaled to account for differences in synaptic receptor number. Traces were filtered to those with a 10–90% rise time of less than 0.9 ms and subjected to visual inspection to eliminate obvious artifacts, overlapping mEPSCs or insufficient peak alignment.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, events were detected using a template-based search (Pernía-Andrade et al, 2012), aligned by their point of steepest rise and peak scaled to account for differences in synaptic receptor number. Traces were filtered to those with a 10–90% rise time of less than 0.9 ms and subjected to visual inspection to eliminate obvious artifacts, overlapping mEPSCs or insufficient peak alignment.…”
Section: Methodsmentioning
confidence: 99%
“…A deconvolution-based algorithm was implemented according to Pernía-Andrade et al (2012). The basic idea is to describe the recorded signal r ( t ) as a convolution h ( t ) of the time course of event onsets f ( t ) with the time course of a typical event p ( t ): h(t)=0tf(tt)p(t)dt, where f ( t ) describes event onsets by the Dirac delta function: f(t)=δ(tt0)={leftfor t = t0,left0for tt0,, where t 0 is the time point of the onset of an event.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore examined EPSCs under voltageclamp conditions at a holding potential of -70 mV, close to the reversal potential of GABA A R-mediated IPSCs (Figures 3A-3D; Table 1). EPSC detection (Pernía-Andrade et al, 2012) followed by kinetic analysis revealed that GCs in vivo in both anesthetized and awake rats were exposed to a high-frequency excitatory phasic input ( Figures 3A and 3B). On average, the peak amplitude of individual EPSCs was 8.8 ± 0.7 pA in anesthetized rats and 21.3 ± 2.4 pA in awake rats (15 and 13 cells, respectively; p < 0.0001; Figure 3C).…”
Section: Synaptic Excitation Of Gcs In Vivomentioning
confidence: 99%
“…EPSCs were detected by a deconvolution-based algorithm (Pernía-Andrade et al, 2012). This procedure is particularly suitable for analysis of synaptic events in vivo, because of its high temporal resolution.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation